Estudo experimental e análise da viabilidade do emprego do pó de mármore para a produção de concreto auto-adensável - Santos, Adriana Padilha dos (2012)
Most industrial processes are sources of waste, damaging the environmental. The use of industrial waste in Construction presents itself as an excellent alternative for reducing environmental impact and contributing to sustainable development, considering that the Construction is the sector of technological activity that consumes large volumes of natural resources and seems to be a best suited to absorb the waste.The residue generated from the processing of stone (marble powder) is resulting from the sawing blocks of rock plates, sawdust, about 25% to 30% of the block is transformed into a powder, which in most cases, is deposited in the courtyards of the companies disposed of or clandestine way, as in roadsides. For these problems and because of the high cost of the CAA, this experiment was done to investigate the feasibility of its use in concrete with replacement levels of 4% marble powder on the mass of cement.For the concretes were evaluated properties of hardened concrete (compressive strength) and durability parameters (absorption by immersion). The analysis shows that the residue of cut granite does not present risks that its use as an addition in concrete is technically feasible, and that 4% replacement performs better without any interference by comparing the strength of concrete with silica fume.